International trade and income in Malawi: a co-integration and causality approach - Matchaya, Greenwell C.; Chilonda, Pius; Nhelengethwa, Sibusiso (2013)
This paper investigates causal relationships between exports, imports, and economic growth in Malawi over the period 1961-2010. These relationships are examined using the Johansen frameworks for co-integration whereas the Vector Error Correction (VECM) framework is further used to provide estimates for both short-run and long-run dynamics in the series under study. The empirical results, including the impulse responses support the export-led economic growth and export driven imports hypotheses in the long run, but they provide no evidence of any economic growth-driven exports. These results strongly support the role of international trade in Malawi's economic development and hence policies that seek to facilitate Malawi's trade within and outside the SADC regional would be worthwhile to pursue.